Book Reviews. Issue 1 (1st August 2018) - Cooper, Patrick K.; Goodrich, Andrew
The Cambridge Companion to Hip-Hop, Justin A. Williams (2015)Cambridge, UK: Cambridge University Press, 370 pp., ISBN: 9781107643864, p/bk, $30.99Rebel Music: Resistance Through Hip Hop and Punk, P. Parmar, A. J. Nocella, S. Robertson and M. Diaz (eds) (2015)Charlotte, NC: Information Age Publishing, 164 pp., ISBN: 9781623969097, p/bk, $45.99 USD